2004
DOI: 10.3758/bf03195859
|View full text |Cite
|
Sign up to set email alerts
|

Word length, phonemic, and visual similarity effects in poor and normal readers

Abstract: A.M.M. is now at the University of York. The work was conducted while A.M.M. was a PhD student at the University of St. Andrews. We thank the Primary 3 pupils and staff at Glebelands Primary School in Dundee. A special mention is also due the pupils and their teachers at Clermiston and Craiglockhart reading units in Edinburgh for their support and assistance with this and other projects over the years. Correspondence should be addressed to R. S. Johnston, Department of Psychology, University of Hull, Hull HU6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 52 publications
4
19
1
2
Order By: Relevance
“…The authors concluded that the poor readers rely on visual strategies in situations where phonological coding is not obligatory. This conclusion was confirmed in a more recent followup study (McNeil & Johnston, 2004). Here, the reading age controls showed clear effects of phonemic similarity and word length with pictorial presentation, whereas the poor readers showed no word length effect and a reduced phonemic similarity effect.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The authors concluded that the poor readers rely on visual strategies in situations where phonological coding is not obligatory. This conclusion was confirmed in a more recent followup study (McNeil & Johnston, 2004). Here, the reading age controls showed clear effects of phonemic similarity and word length with pictorial presentation, whereas the poor readers showed no word length effect and a reduced phonemic similarity effect.…”
Section: Introductionsupporting
confidence: 75%
“…Because of important methodological differences, the reasons for these discrepancies are difficult to explain. For example, McNeil and Johnston (2004) used four-item lists and took number of sequences correctly recalled as performance measure, whereas Irausquin and de Gelder (1997) used six-item lists for roughly the same age group and proportion correct per serial position as dependent variable. Furthermore, Irausquin and de Gelder's (1997) participant groups were equated for digit span.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the present study, taken together with those of others (Macaruso et al, 1996;McNeil & Johnston, 2004), may have direct implications for understanding the nature of poor readers' slowness in learning to recognize new words. In normal readers, repeated exposure to words or other printed stimuli that have verbal labels usually leads to the development of interconnections between the visual and the verbal modalities (Swanson, 1987).…”
Section: Discussionmentioning
confidence: 89%
“…Consequently, their word recognition may have been less well underpinned by connections in memory between the letters in the spelling and the phonemes in the pronunciation (Ehri, 1992). In another study, these same poor readers showed a visual bias in their memory codes for pictorial stimuli (McNeil & Johnston, 2004). In serial order recall tasks, when children (and adults) encode pictorial information verbally and rehearse the items, they show word length effects (i.e., better recall of short than of long words; Baddeley, Thomson, & Buchanan, 1975) and phonemic similarity effects (i.e., better recall of phonologically dissimilar than of similar items; Baddeley, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation